STRATEGY FOR HOLISTIC APPROACH IN THE MANAGEMENT OF SOMATIC PATIENT WITH ANXIETY AND DEPRESSION - Kornatskyy, V.M.; Мороз, Д.М. (World of Medicine and Biology, 2015)
Multіmorbidic patient is currently the most complex and important problem of the health system, especially in conditions of chronic stress, which is a prerequisite of mental health disorder. In the management of somatic patients the psychological component as a possible cause of poor health is underestimated, and there is no model of integrated medical and psychological care.